Edukasi Energi Alternatif Kepada Warga Masyarakat Dusun Kappe, Kecamatan Duampanua, Kabupaten Pinrang - Said, Sukmawati; Rosita; Ihfa Indira Nurnaifah (MAMMIRI: JURNAL PENGABDIAN MASYARAKAT, 2024)
Alternative energy has become a highly discussed topic nowadays. Therefore, the introduction of alternative energy sources must continue to be socialized to the general public to make it common place to use alternative energy in daily life. One of interesting alternative energy source for activity implementers is used cooking oil as an alternative energy source. The implementation of an alternative energy education seminar, particularly on used cooking oil, for the community of Dusun Kappe, Pinrang Regency, has successfully increased the curiosity of the community, as seen from the interest of community members attending and the numerous questions raised during the Q&A session. Thus, activities like this can be continued so that the general public can effectively utilize environmentally friendly materials available in nature as alternative energy sources that have undergone testing and feasibility assessments